Complete and Circularized Bacterial Genome Sequence of Gordonia sp. Strain X0973 - Gulvik, Christopher A. (Microbiol Resour Announc, 2021)
Gordonia sp. strain X0973 is a Gram-positive, weakly acid-fast, aerobic actinomycete obtained from a human abscess with Gordonia araii NBRC 100433(T) as its closest phylogenetic neighbor. Here, we report using Illumina MiSeq and PacBio reads to assemble the complete and circular genome sequence of 3.75 Mbp with 3,601 predicted coding sequences.